A large, locally aggressive giant cell tumour arising from the laryngeal cartilage: A Rare Case Report - Riaz, Umar; Wali, Hadia; Shahid Ansari, Shayan; Hameed, Zujajah; Muhammad Saqib (Journal of the Pakistan Medical Association, 2024)
Giant cell tumour is a growth predominantly found in long bones of the body. Giant cell tumour has a rare occurrence in the head and neck. A case of a 31 year old male with no known comorbidities at the ENT Department, Shifa International Hospital, Islamabad presented with anterior neck swelling and hoarseness of voice. Patient was diagnosed as having Giant Cell Tumour of Larynx (GTCL) proven on FNA cytology and post-operative biopsy. GCTL is an uncommon entity with only 45 reported cases in the world. Key Words: Giant Cell Tumor, Laryngeal Cancer, Thyroid Cartilage, Laryngectomy.